THE EFFECT OF NI CONCENTRATION AND ADDITION OF ZR ON HIGH-ENTROPY SUPERALLOY FENICRALCO: A FIRST-PRINCIPLES STUDY - Nugraha, Farhan
The demand for materials with long service life and low material cost for high temperature applications is increasing. High-entropy superalloy is a classification of material that have the characteristics of both superalloy and high-entropy alloy. These alloys are widely developed to improve cost efficiency and performance especially in high temperature applications. However, the high concentration of Ni in these alloys increases the raw material cost significantly. The utilization of the cheaper element Fe as an alloy base is a good alternative to be applied. In addition, the potential of adding dopant elements, such as Zr, which has been shown can increase strength in conventional superalloy has not been investigated in this alloy. Therefore, this study aims to conduct modelling through the first-principles method to determine the effect of decreasing Ni concentration and adding Zr on lattice parameters, elasticity properties, stacking fault energy (SFE) values, electronic structure, and provide design guidance for Fe-based FeNiCrAlCo high-entropy superalloy. Simulations were performed with CASTEP software using the first-principles density functional theory method. Elasticity constant calculations were performed on 1x1x2 face-centered cubic (FCC) supercells. Elasticity properties were determined by Voigt-Reuss-Hill approximation using elasticity constant data. Geometry optimization, calculation of stacking fault energy values, and electronic structure determination were performed on the 1x1x4 FCC supercell. The stacking fault energy value is calculated based on the structure with a vacuum space of 10 Å and the addition of stacking faults. Electronic structure analysis is performed to determine the charge density difference in the form of contours of charge accumulation and depletion zones and density of states. The design guidelines were explained based on the parameters generated in this study. Decreasing the Ni concentration and adding Zr tended to increase the lattice parameters and produced good elasticity and ductility properties for the alloy. Reduction in Ni concentration by 4.17 wt.% accompanied by an increase in Fe, Cr, Co, and Zr concentrations decreased the value of stacking fault energy. Whereas, the reduction in Ni concentration accompanied by an increase in Al concentration increased the stacking fault energy value. The electronic structure analysis showed that decreasing Ni concentration by 4.17 at.%, while increasing Fe, Cr, Co, and Zr, increased the charge accumulation zone and decreased the density of states. Based on these results, alloy design could be done by reducing Ni concentration which could still provide good ductility and reduced the value of stacking fault energy, while an increase in Cr concentration tended to increase strength, ductility, and hardness or Zr concentration to reduce the stacking fault energy to an optimum.